2020
DOI: 10.3390/app10082873
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of the Allelochemical Juglone on Growth of Harmful and Non-Target Freshwater Algae

Abstract: Allelopathy has been applied to control nuisance algae in aquatic systems, but the effects of allelochemicals on the broad spectrum of algae are not well understood. We investigate algicidal effects of the allelochemical juglone on the bloom-forming, harmful algae Microcystis aeruginosa and Stephanodiscus hantzschii, and on several non-target algal species including cyanobacteria (Anabaena flos–aquae, Oscillatoria curviceps, and Phormidium subfuscum), diatoms (Asterionella formosa, Fragilaria crotonensis, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Stimulation of a particular trait in one species at a given concentration may not be the same in another species. For example, at 5.7 µM, juglone inhibited the growth of Stephanodiscus hantzschii by more than 60%, while at the same time exhibited hormetic activity on three other diatoms, Asterionella formosa, Fragilaria crotonensis, and Synedra acus [92]. Along the same lines, Table 1 summarizes a range of reported inhibitory and stimulatory effects of juglone, juglone-producing species, and juglone-containing materials on various plant species.…”
Section: Juglone As a Biostimulantmentioning
confidence: 90%
See 3 more Smart Citations
“…Stimulation of a particular trait in one species at a given concentration may not be the same in another species. For example, at 5.7 µM, juglone inhibited the growth of Stephanodiscus hantzschii by more than 60%, while at the same time exhibited hormetic activity on three other diatoms, Asterionella formosa, Fragilaria crotonensis, and Synedra acus [92]. Along the same lines, Table 1 summarizes a range of reported inhibitory and stimulatory effects of juglone, juglone-producing species, and juglone-containing materials on various plant species.…”
Section: Juglone As a Biostimulantmentioning
confidence: 90%
“…Growth of Streptophytic (Closterium acerosum, Micrasterias thomasiana, and Spirogyra grevilleana) and chlorophytic (Pandorina morum and Eudorina californica) freshwater green algae is also inhibited by juglone at concentrations ranging from 0.1-1 mM [91]. Interestingly, lower concentrations, 0.1-1 mg L −1 (0.57-5.7 µM), were found to stimulate growth of chlorophytic freshwater green algae Chlorella vulgaris, Scenedesmus ecornis, and S. quadricauda and the freshwater diatoms Asterionella formosa, Fragilaria crotonensis, and Synedra acus [92]. Park et al [92] also found that juglone can inhibit the harmful bloom-forming nuisance cyanobacterium Microcystis aeruginosa and the freshwater diatom Stephanodiscus hantzschii by up to 93% and 75%, respectively, at 1 mg L −1 (5.7 µM).…”
Section: Algacidal Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Low, sub-NOAEL concentrations of contaminants may also lead to changes in the species composition of algal assemblages. ,, They may even impair the chemosensory system of organisms depending on dissolved chemical cues for their survival by depleting inorganic carbon and highly elevating pH due to increased photosynthesis. , For example, low, environmentally relevant, stimulatory doses of a mixture of ciprofloxacin, sulfamethoxazole, and tetracycline antibiotics could enhance the competitiveness and increase the proportion of the “harmful” M. aeruginosa in a mixed culture of four phytoplankton species . Similarly, algaecidal hydrogen peroxide at 0.2 mg L –1 increased and at 0.5–1.5 mg L –1 decreased the relative abundance of Anabeana , Microcystis , and Oscillatoria within a community of cyanobacteria and the relative abundance of Cyanobacteria within a prokaryotic community .…”
Section: Unanswered Questions and The Path Forwardmentioning
confidence: 99%